The Effect Of 3D Printing Parameters On The Properties Of Thermoplastic Polyurethane Scaffold - Chai, Pei Ying (Universiti Sains Malaysia, 2022)
In the field of tissue engineering, the scaffold is necessary to provide a favorable environment for tissue regeneration. The scaffold should replicate the mechanical characteristics of the tissue as closely as possible. One of the most popular additive manufacturing processes that can be utilized to create scaffolds is fused deposition modelling (FDM). The printing parameters have a significant impact on the morphology and mechanical properties of the printed scaffold. The first objective of this project is the characterization of TPU-72D filament in terms of tensile strength, thermal properties, melt flow rate and hardness. The second objective is to investigate the effect of 3D printing parameters on the morphology and the compression properties of TPU scaffold. The important 3D printing parameters of bed temperature, nozzle temperature, printing speed, and infill density were chosen. The scaffold has been constructed by 72 shore D thermoplastic polyurethane (TPU). Differential scanning calorimetry shows the presence of soft segment (SS) and hard segment (HS) in the structure but the hardness decreases to 50 shore D lower the flow rate. Increase in the TB, TN and ID could increase the strength of the scaffold, while increase in Sp decrease the strength of the scaffold. The best setting of input parameters for compressive modulus and compressive strength are TB 40°C, TN235°C, SP 35mm/s, and ID 100%. Combination of 30-225-50-30 printing parameter gives a closer dimension to the original design than 40-235-35-100 printing parameter. 4T is the best surface finish part among these tissue engineering (TE) scaffolds.